Chapter 17: Made to measure: how central banks deliver performances of their worth and why unconventional monetary policy is reversing the burden of proof - Walter, Timo (Edward Elgar Publishing, 2024)
Central banking is frequently considered a prototype case of governance subject to continuous and public performance measurement. However, central banks' near-exclusive preoccupation with preserving price stability as the overriding measure of success of their monetary policy is a rather recent (post-1970s) fabrication - and one that has come under increasing strain since the 'unconventional' monetary policies initiated during the 2007-09 global financial crises have become perennial. This chapter retraces how central banks have evolved into a close symbiosis with 'unfettered' finance as they attempted to (re)construct their independence around the public performance of monetary policy's effectiveness in securing price stability. It shows how this symbiosis now confronts central banks with a dilemma: while 'unconventional' policies are necessary to secure the financial stability on which the performance of 'inflation targeting' depends, they continuously highlight the fungibility of central banks' power and undermine the narrow focus on price stability around which their legitimacy is constructed.